Development of Location-Based Services in Smart Systems: A Literature Review - Mhd. Hanafi; Firdaus (Universitas Muhammadiyah Surakarta, 2025)
Location-Based Services (LBS) are technologies that utilize user location data to provide relevant location-based information. This study aims to examine various LBS applications in smart systems through a review of previous literature. LBS are applied in both outdoor and indoor environments. Outdoor LBS typically use Global Positioning System (GPS) technology for applications such as attendance systems, local business searches, transportation, and healthcare services. Meanwhile, indoor LBS use technologies like Pedestrian Dead Reckoning (PDR) and Simultaneous Localization and Mapping (SLAM) to navigate environments where GPS signals are obstructed. This study also identifies the use of hybrid systems that integrate both indoor and outdoor LBS to ensure consistent service. In addition, challenges related to accuracy, privacy, and energy efficiency in LBS applications across various sectors are discussed. The findings of this research highlight the significant potential of LBS in supporting smart systems while emphasizing the need for further research to address existing challenges, particularly in technology integration and privacy improvements. The implementation of hybrid systems combining indoor and outdoor technologies is expected to provide a more comprehensive solution for future development.